1995
DOI: 10.1002/jsfa.2740680217
|View full text |Cite
|
Sign up to set email alerts
|

High levels of glycoalkaloids in the established swedish potato variety magnum bonum

Abstract: In 1986, potentially toxic levels of the glycoalkaloids a-solanine and a-chaconine were unexpectedly found in tubers of the established Swedish consumer potato variety Magnum Bonum, leading to the imposition of a conditional sales ban on such potatoes. The combined amounts of a-solanine and a-chaconine in more than 300 commercial lots of Magnum Bonum potatoes analysed as a consequence of the ban ranged from 61 to 665 mg kg-' fresh weight with an average of 254 mg kg-'. Sixty-six percent of the samples exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…The glycoalkaloid results for British Queen observed here are consistent with those of Hellena Ès et al, 12 who found higher than normal glycoalkaloid levels in tubers of cvs British Queen and Magnum Bonum grown as commercial crops in Sweden in 1986. The authors correlated their results with the abnormally wet and cold conditions close to harvest and stated that the Table 2 combination of cold weather and heavy precipitation might be important rather than each individual stress.…”
Section: Effect Of Waterlogging At 12/9°c On Glycoalkaloid Levelssupporting
confidence: 94%
“…The glycoalkaloid results for British Queen observed here are consistent with those of Hellena Ès et al, 12 who found higher than normal glycoalkaloid levels in tubers of cvs British Queen and Magnum Bonum grown as commercial crops in Sweden in 1986. The authors correlated their results with the abnormally wet and cold conditions close to harvest and stated that the Table 2 combination of cold weather and heavy precipitation might be important rather than each individual stress.…”
Section: Effect Of Waterlogging At 12/9°c On Glycoalkaloid Levelssupporting
confidence: 94%
“…This finding is contrary to the findings of Zrůst et al (2000), who reported high levels of TGA during the dry, warm sunshine and rich growing season. Explanation, however, can offer a hypothesis of the authors Hellenäs et al (1995), which was published in connection with excluding Swedish cv. Magnum Bonum from the market because toxic levels of TGA were found in it (the contents of more than 300 analysed commercial samples reached average values of 254 mg TGA/kg FM).…”
Section: Content Of Glycoalkaloidsmentioning
confidence: 99%
“…Such a response is now well established and has been reported by workers elsewhere. 11,13,15,16 Cultivar Kestrel proved the most light-sensitive genotype, and cv Maris Piper relatively light-insensitive. Initial glycoalkaloid concentrations in both cultivars were similar at 71.5 and 95.2 mg kg À1 FW respectively, but rates of accumulation thereafter differed markedly (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Glycoalkaloids were extracted from each individual tuber as described in Ref 15, and quanti®ed using high-pressure liquid chromatography. 16 …”
Section: Plant Materialsmentioning
confidence: 97%